1980
DOI: 10.1113/jphysiol.1980.sp013413
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and rhythm‐generating mechanisms governing the sudomotor and vasoconstrictor outflow in human cutaneous nerves.

Abstract: SUMMARY1. Recordings of multiunit sympathetic activity were made from human nerve fascicles supplying hairy and glabrous skin of the extremities in healthy subjects exposed to different ambient temperatures. Sudomotor and vasomotor events accompanying the neural activity were monitored by simultaneous recordings of electrodermal and pulse plethysmographic events (Pleth) in the neural innervation zones.2. By exposing the subject to warm (43 00) or cold (15 00) environments, it was possible to obtain a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
244
3
3

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(275 citation statements)
references
References 13 publications
(15 reference statements)
17
244
3
3
Order By: Relevance
“…Care was taken to ascertain that neither in the input stages nor in the tape recorder there was any significant 'cross-talk' between the two micro-electrode recording channels. Since a previous study dealt with the correlation between the neural sympathetic activity and the accompanying electrodermal and plethysmographic events (Bini et al 1980) only the mean voltage ('integrated') neurograms are shown in the present paper (with omission of electrodermal and plethysmographic recordings). The double nerve recording sites could often be maintained for several hours.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Care was taken to ascertain that neither in the input stages nor in the tape recorder there was any significant 'cross-talk' between the two micro-electrode recording channels. Since a previous study dealt with the correlation between the neural sympathetic activity and the accompanying electrodermal and plethysmographic events (Bini et al 1980) only the mean voltage ('integrated') neurograms are shown in the present paper (with omission of electrodermal and plethysmographic recordings). The double nerve recording sites could often be maintained for several hours.…”
Section: Techniquementioning
confidence: 99%
“…The double nerve recording sites could often be maintained for several hours. Unless otherwise stated the subject was resting in a comfortable position while the environmental temperature was changed in the ways previously described (Bini et al 1980). When the subject was lying inside the hypothermia box the arm on which the recordings were made passed through an opening in the box and was (from the axillary region) exposed to a constant room temperature of 22-24 0C.…”
Section: Techniquementioning
confidence: 99%
“…In addition, inspiratory and arousal stimuli are usually followed by a strong burst of skin nerve sympathetic activity. Emotional stress may evoke repeated bursts [1,8,17]. The evidence for the sympathetic nature of these activities has been summarized by Vallbo et al [33].…”
mentioning
confidence: 99%
“…The two types of fibers are intermingled, and it is difficult to record pure vasoconstrictor impulses isolated from sudom otor impulses. Changing the environmental temperature makes it possible to obtain a selective activa- tion of vasoconstrictor impulses only (9). In oth er words, with a lower ambient temperature, the vasoconstrictor impulses become more dom inan t becau se the sudomotor impulses are suppressed.…”
Section: Discussionmentioning
confidence: 99%